APLIKASI FORMULASI DOSIS MIKORIZA DENGAN KONSENTRASI AIR KELAPA DAN PENGARUHNYA TERHADAP PERTUMBUHAN BIBIT KAKAO (Theobroma cacao L.) DI MEDIUM ULTISOL - Diana Putri Nurul Utami; Armaini Armaini; Sukemi Indra Saputra (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2021)
The problem in large scale cacao nurseries is the limitated top soil as a planting medium. The use of ultisol as a medium requires improvement with the aim of producing quality cocoa seeds.The study used a non factory completely randomized design (CRD) with 9 treatments of mycorrhizal (g) formulations with coconut water (%): 5 g and 50%, 7,5 g and 50%, 10 g and 50%, 5 g and 75%, 7,5 g and 75%, 10 g and 75%, 5 g and 100%, 7,5 g and 100%, 10 g and 100%. The result showed that the treatment mycorrhizal with coconut water had an effect on seedling height, root volume, and dry weight of cocoa seeds. Mycorrhizal dose of 10 g per polybag with 50% coconut water gave the best cocoa seed yield and could increase number of leaves, seedling weight, root volume and dry weight of cocoa seedlings. Key words:Nursery, Theobroma cacao L., Mycorrhiza, Coconut water, Ultisol